2021
DOI: 10.1101/2021.03.14.435266
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A free-living protist that lacks canonical eukaryotic DNA replication and segregation systems

Abstract: Cells must replicate and segregate their DNA with precision. In eukaryotes, these processes are part of a regulated cell-cycle that begins at S-phase with the replication of DNA and ends after M-phase. Previous studies showed that these processes were present in the last eukaryotic common ancestor and the core parts of their molecular systems are conserved across eukaryotic diversity. However, some unicellular parasites, such as the metamonad Giardia intestinalis, have secondarily lost components of the DNA pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 165 publications
(261 reference statements)
0
5
0
Order By: Relevance
“…Repeat analysis using RepeatModeler suggested that around 45.97 % of the new genome assembly is represented by various types of repeats ( Table 2 ), higher than the initially reported 37–38 % [ 5, 16 ] and consistent with the size increase of the assembly. In metamonads, the percentage of repetitive elements varies from 4 % in Carpediemonas frisia up to approximately 67 % in Trichomonas vaginalis [ 16 ], placing the genome of M. exilis on an average measure of repetitive elements-content. Yet, the relative composition of repetitive elements is very different to other metamonads, containing the highest percentage of unclassified repeats ( Table 2 ) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Repeat analysis using RepeatModeler suggested that around 45.97 % of the new genome assembly is represented by various types of repeats ( Table 2 ), higher than the initially reported 37–38 % [ 5, 16 ] and consistent with the size increase of the assembly. In metamonads, the percentage of repetitive elements varies from 4 % in Carpediemonas frisia up to approximately 67 % in Trichomonas vaginalis [ 16 ], placing the genome of M. exilis on an average measure of repetitive elements-content. Yet, the relative composition of repetitive elements is very different to other metamonads, containing the highest percentage of unclassified repeats ( Table 2 ) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In metamonads, the percentage of repetitive elements varies from 4 % in Carpediemonas frisia up to approximately 67 % in Trichomonas vaginalis [ 16 ], placing the genome of M. exilis on an average measure of repetitive elements-content. Yet, the relative composition of repetitive elements is very different to other metamonads, containing the highest percentage of unclassified repeats ( Table 2 ) [ 16 ]. While these could represent some new types of repeats, we hypothesise that some of the unclassified repeats may be misidentified and may represent highly expanded protein families in the genome of M. exilis, such as protein tyrosine kinases, which tend to overlap with unclassified repeats ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Query protein sequences for individual subunits from each ESCRT sub-complex from various pan-eukaryotic representatives were obtained and aligned using MUSCLE v3. 8.31 (Additional Material 24-Supplementary Table 4 ) [ 45 , 69 83 ]. Resulting alignments were used to generate Hidden Markov Models using the hmmbuild option available through the HMMER 3.1.b1 package and HMMER searches into all Fornicata genomes and transcriptomes using the hmmsearch tool with an e-value cutoff set to 0.01 [ 84 ].…”
Section: Methodsmentioning
confidence: 99%
“…While these are much lower than what is typically expected of a eukaryotic genome from animal, plant, or fungal lineages (i.e., 85-95%), low BUSCO scores in Giardia are a drawback of limited inclusion of diverse protist lineages within the eukaryote_odb10 database. In general, metamonad lineages are highly divergent in their sequences and ancestrally lack many of the proteins present in model eukaryotes, and therefore all suffer from poor BUSCO scores [42][43][44]. Instead of using these as absolute measures, BUSCO scores were evaluated against those published for other Giardia assemblies.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%